2008
DOI: 10.1002/marc.200700638
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Two Different Isotropic Phases as a Reason for Bistable Phase Behavior of an LC Side‐Chain Polymethacrylate

Abstract: An isotropic melt of a chiral side‐chain polymethacrylate was studied by electric birefringence technique. A phase transition between two different isotropic phases was detected by Kerr effect and confirmed by WAXS measurements. The obtained experimental data can explain the previously reported bistable phase behavior of the polymer, as conventional Sm A phase is formed in slow cooling whereas a TGB‐like, optically isotropic mesophase in fast cooling.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The electro-optical properties of an isotropic melt above the nematic-isotropic melt phase transition temperature were studied by considering the Kerr effect, which serves as a tool for examining phase transitions in mesogens [9,10]. The electric field-induced birefringence ΔnE is related to the Kerr constant K and the electric field strength E by the Kerr equation: ΔnE = KE 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The electro-optical properties of an isotropic melt above the nematic-isotropic melt phase transition temperature were studied by considering the Kerr effect, which serves as a tool for examining phase transitions in mesogens [9,10]. The electric field-induced birefringence ΔnE is related to the Kerr constant K and the electric field strength E by the Kerr equation: ΔnE = KE 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Photoinduced dichroism, optical anisotropy and photorecording properties in these chiral Azo-polymers 6, 7 had been triggered by the anisotropic angular distribution of trans and cis isomers [ 159 , 160 , 161 , 162 ]. Furthermore, a chiral Azo-homopolymer 8 with an Azo chromophore bearing a chiral terminal chain was also reported by their group, which exhibited a photoinduced birefringence property and smectic A (SmA) or a twist grain boundary A* (TGBA*)-like bistable phase depending on the thermal history of the polymer (in particular, the cooling rate from the isotropic state) [ 163 , 164 , 165 ]. It was reported that this bistable phase behavior is related to two different isotropic states.…”
Section: Supramolecular Chirality Of Azo-polymers Constructed By Pmentioning
confidence: 99%